2014
DOI: 10.1007/s00261-014-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of duodenal adenocarcinomas: a comprehensive review for the radiologist

Abstract: Duodenal adenocarcinomas are the most common duodenal tumors, and represent 15-25% of small bowel carcinomas. Their management differs from other small bowel tumors, with imaging playing a very important role. In this article, we provide a comprehensive review of the diagnosis and management of duodenal adenocarcinomas, emphasizing the role of the radiologist in the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 64 publications
(104 reference statements)
0
22
0
1
Order By: Relevance
“…Although they are considered to be very rare, there are studies that have shown that primary duodenal tumors are found in 15-25 % of cases of malignant tumors of the small intestine [5][6][7]. In the study group, primary duodenal malignant tumors were found in a number of 25 cases representing 17 % of all malignancies studied; in terms of pathology were adenocarcinomas.…”
Section: Discussionmentioning
confidence: 86%
“…Although they are considered to be very rare, there are studies that have shown that primary duodenal tumors are found in 15-25 % of cases of malignant tumors of the small intestine [5][6][7]. In the study group, primary duodenal malignant tumors were found in a number of 25 cases representing 17 % of all malignancies studied; in terms of pathology were adenocarcinomas.…”
Section: Discussionmentioning
confidence: 86%
“…Pancreaticoduodenectomy has an overall survival benefit according to some reports [1]. However, segmental resection is recommended for the horizontal and ascending duodenum because it has a reduced complication rate and achieves margin-negative resection [7]. Primary tumor and adequate regional lymph nodes should be completely resected during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Radical resection of distal stomach and duodenal bulb lesions is required for duodenal bulb adenocarcinoma close to the pyloric canal. As in the case of malignancy in the duodenal bulb with other involved parts or involvement of the descending part of the duodenum, pancreaticoduodenectomy is preferred [7]. Pancreaticoduodenectomy has an overall survival benefit according to some reports [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations